Inkheart [compact disc, unabridged] - Funke, Cornelia, 1958- (Random House/Listening Library, 2003)
Twelve-year-old Meggie learns that her father, who repairs and binds books for a living, can "read" fictional characters to life when one of those characters abducts him and tries to force him into service.